Preoperative Preparation of Patients with Anemia before Shoulder Replacement - S. V. Sokolov; V. А. Gluschenko (Вестник анестезиологии и реаниматологии, 2021)
The preoperative anemia in patients increases the risk of perioperative blood transfusion, myocardial infarction, ischemic stroke, acute kidney injury, and higher nosocomial and 30-day mortality, lengthens the duration of treatment, and increases the risk of re-hospitalization.The objective: to improve treatment results of patients after revision shoulder replacement through management of preoperative anemia.Subjects and methods. 170 medical files of patients who underwent revision shoulder replacement from 2014 to 2021 were retrospectively analyzed. On the day when they were examined by the physician, all patients had blood hemoglobin level below 130 g/l. The patients were divided into two groups that were comparable in their characteristics. Patients of the Main Group (n = 90) received preoperative preparation with iron carboxymaltate in combination with recombinant human erythropoietin 4 weeks before the expected date of surgery. Patients of the Control Group (n = 80) did not have any specific preparation.Results. The data obtained showed that the volume of intraoperative and postoperative drainage blood loss did not differ statistically between the groups; hemoglobin blood level in patients from the Main Group was statistically significantly higher both before the surgery and on the first day after it, and no hemotransfusion was indicated. In the Control Group, a statistically significantly greater decrease in hemoglobin level was observed in the postoperative period; 3 (3.8%) patients in the Control Group required RBC-transfusion. Complications in the early postoperative period (myocardial infarction, pulmonary embolism, and cardiac arrhythmia) were significantly less frequent in the Main Group versus the Control one (4.5% of cases vs. 8.8%; p < 0.05).Conclusion. The use of iron carboxymaltate at the dose of 1,000 mg once and, if necessary, repeatedly in 14 days in combination with recombinant human erythropoietin at the dose of 150 IU/kg allows preparing patients for revision shoulder replacement within the period from two weeks to one month. Preoperative management of anemia until the hemoglobin concentration reaches 130 g/l using the proposed regimen can significantly reduce the need for blood transfusion and frequency of somatic complications in the early postoperative period.